A Social Return on Investment evaluation of the Emotion-Mind Dynamic (EMD) two phase social prescribing life coaching intervention to support mental health and wellbeing. - Makanjuola, Abraham; Lynch, Mary; Hartfiel, Ned; Cuthbert, Andrew; Edwards, Rhiannon Tudor (International Journal of Population Data Science, 2022)
Background The COVID-19 pandemic has created excess weighting lists to access Mental Health Services in the UK (Stats Wales, 2021). It is important to find effective solutions to alleviate the pressures that Mental Health services experience. The NHS Five Year Forward View encourages the development of new social prescribing empowerment-based interventions to supplement existing mental health programmes (Mental Health Taskforce, 2016). The EmotionMind Dynamic (EMD) is a lifestyle coaching programme that supports individuals suffering from anxiety or depression referred from the health and social care sectors. EMD offers a unique, non-clinical mixed-modality approach combining coaching, mentoring, counselling skills, teaching and mindfulness. Methods Social Return On Investment (SROI) methodology is applied to evaluate the EMD service. The aim of the SROI analysis is to develop a programme-level theory of change to establish how inputs (e.g. costs, staffing) are converted into outputs (e.g. numbers of clients seen), and subsequently into outcomes that matter to clients impacted by EMD service (e.g. improved mental wellbeing). Wellbeing valuation will quantify and value outcomes using two value sets. The SROI mixed-method approach collects quantitative and qualitative data from questionnaires and interviews with former face-to-face EMD clients as well a new clients, undertaking the online blended learning programme. Findings Initial results indicate that the social prescribing face-to-face EMD programme generated positive social value ratios ranging from £9 to £23 for every £1 invested. In addition, the General Self-Efficacy Scale (GSES) which measures participant’s self-reported self-efficacy and confidence indicated that the face-to-face EMD participants experienced improved mental wellbeing and resilience as a result of participating in the EMD lifestyle coaching programme. Sensitivity analyses was conducted with Social Value Bank (SVB) figures for improved confidence and confirmed assumptions that former EMD clients experienced positive mental wellbeing improvements as a result of undertaking the lifestyle coaching programme. Conclusions This is the first study to undertake an SROI analysis of a social prescribing lifestyle coaching programme aimed at improving mental wellbeing and resilience. Phase one of this novel SROI study of the face-to-face EMD clients indicates that the EMD lifestyle coaching programme has the potential to generate positive social value ratios. Phase two analysis of the online EMD blended learning programme will compare the effectiveness of the two lifestyle coaching formats: face to face and the online blended format to improve mental wellbeing and self-efficacy by participating in this innovative lifestyle coaching programme.